Resposta da soja (Glycine max (L.) Merrill) a ação de bioestimulante - Klahold, Celestina Alflen (2005)
Soybeans is a crop of prominence in the national grain production. The production growth and the increasing in the productivity capacity of soybeans are connected to the scientific and technological advances in the productive sector. One of theses advances is the biostimulants uses. Thus this paper aimed to verify the effect of the biostumulant Stimulate® applied via seed and the leaves pulverization and the combination of these two ways in the development and yield of the soybeans. The experiment was performed in vases with a plastic cover umbrella kind, with sides open up to 2,5 m of height in the region called Linha São Domingos a region in Toledo Municipality, Paraná. Randomized block experimental design was used with four blocks with the treatments obtained through the combination of different biostimulant doses applied, via leaves and seeds. During the experiment four plant collections were done per treatment: 15 DAE (days after emergence) (stage V3), 58 DAE (stage R2), 73 DAE (stage R3) and 129 DAE (stage R9). Through the results it was possible to conclude that the applications of Stimulate® via seed did not promote the alterations in the evaluated variables at the 15 and 58 DAE in the soybeans crop. At the 73 DAE the application of the biostimulant Stimulate® via seed, via leaves and in the combination of the two ways resulted in positive effects on the dry mass of the flowers, dry mass of the root, ratio root/shoot and the number of leaves. The application of the biostimulant promoted increments to the numbers of beans, grains and the production per plant, highliting the treatments 3 (0,0 mL 0,5 Kg-1 (AS) + 0,150 mL L-1 (APF)), 5 (3,0 mL 0,5 Kg-1 (AS) + 0,0 mL L-1 (APF)), 8 (3,0 mL 0,5 Kg-1 (AS) + 0,225 mL L-1 (APF)) and 10 (5,0 mL Kg-1 (AS) + 0,075 mL L-1 (APF)). The increasing in the number of grains and the beans per plant resulting of the application of the biostimulant led to a lower mass of 100 grains, probably because of the partition of the photoassimilates among the physiological sink.